STIGMASTANE-STEROID FROM THE BARK OF Chisocheton lasiocarfus (Meliaceae) - Nurlelasari Nurlelasari; Fajar Fauzi Abdullah; Nadya Thufaila; Rani Maharani; Desi Harnet; Ace Tatang Hidayat; Unang Supratman (Jurnal Kimia (Journal of Chemistry), 2017)
Stigmastan-steroid, stigma-4-ene-3-on (1) has been isolated from the bark of Chisocheton lansiocarpus. The chemical structure of stigmastan-steroid was identified based on spectroscopic data and by comparison of spectral data obtained previously. The discovery of stigma-4-ene-3-on in C. lansiocarpus was shown in this study for the first time.